Зміни локальної жорсткості судинної стінки у хворих на гіпертонічну хворобу на тлі цукрового діабету 2 типу під впливом антигіпертензивної терапії з дапагліфлозином - Богун, Ангеліна Олексіївна; Bohun, A. O. (Запорізький державний медико-фармацевтичний університет, 2024)
До дослідження залучено 85 хворих на гіпертонічну хворобу (ГХ) ІІ стадії, з яких основну групу склали 37 пацієнтів із ГХ ІІ стадії в поєднанням із цукровим діабетом 2 типу (ЦД), віком від 37 до 77 років (середній вік – 60,4 ± 10,7 років), чоловіків 66,7%. Надалі пацієнтів розподілили на 2 групи - пацієнтів першої групи було рандомізовано до прийому метформіну, а другої групи – до прийому комбінації метформіну із дапагліфлозином. Всі пацієнти отримували співставну антигіпертензивну терапію препаратами першої лінії (перевага надавалась комбінації периндоприлу з індопамидом) та гіполіпідемічну терапію (перевага надавалась аторвастатину/розувастатину). Термін спостереження – 12 тижнів. Група порівняння – хворі на ГХ ІІ стадії без супутнього ЦД (48 осіб віком від 26 до 80 років (середній вік – 55,9 ± 11,2 роки)). The study enrolled 85 patients with stage II hypertension (HTN), of which the main group consisted of 37 patients with stage II (HTN) with accompanying diabetes mellitus (DM) type 2, aged from 37 to 77 years (average age - 60.4 ± 10.7 years), men 66.7%. Further, the patients were divided into 2 groups - patients of the first group were randomized to receive metformin, and the second group - to receive a combination of metformin and dapagliflozin. All patients received comparable antihypertensive therapy with first-line drugs (perindopril and indopamide combination was preferred) and lipid-lowering therapy (atorvastatin/rosuvastatin was preferred). The observation period was 12 weeks. The comparison group consisted of patients with stage II (HTN) without accompanying DM type 2 (48 people aged 26 to 80 years (average age – 55.9 ± 11.2 years)). For the purpose of this work, the influence of risk factors for cardiovascular diseases (CVD), anthropometric data (height, weight, percentage of fat tissue, waist volume), biochemical data (carbohydrate and lipid profile indicators, kidney function) and instrumental data (echocardiography, elastic properties of common carotid arteries (CCA), which were studied during ultrasound examination of carotid arteries (CA) using RF-QIMT, RF-QAS technologies), as well as their changes during two treatment programs. Statistical processing performed using the statistical software package Statistica for Windows 13.0 (StatSoft Inc., USA; license no. JPZ804I382130ARCN10-J) and MedCalc.10.2.0.0 Differences were considered significant at values p < 0.05.
Changes in the local stiffness of the vascular wall in hypertensive patients with type 2 diabetes under the influence of antihypertensive therapy with dapagliflozin
Keywords: гіпертонічна хвороба; цукровий діабет 2 типу; артеріальна жорсткість; дапагліфлозин; інгібітори НЗКТГ 2; артеріальна гіпертензія; систолічна функція; Arterial hypertension; type 2 diabetes mellitus; arterial stiffness; dapagliflozin; inhibitors SGLT2; systolic function